GUIDELINES FOR COORPERETIVE LEARNING MANAGEMENT TO ENHANCE EDUCATIONAL OUTCOMES FOR SMALL PILOT SCHOOLS, CHIANG MAI EDUCATION SANDBOX - Thongluan, Panisa; Pornwieng , Suban (Journal of Buddhist Education and Research (JBER), 2024)
The aims of this study to investigate the problems and needs in cooperative learning management to enhance educational outcomes for small pilot schools, Chiang Mai sandbox. Also, to explore guidelines for cooperative learning management. Moreover, to evaluate the effectiveness of guidelines for cooperative learning management. This research follows a mixed-method approach. Phase 1 used the questionnaire to investigating the issues and needs in cooperative learning management. There are 125 participants in total, including school administrators and teachers from small pilot schools and Chiang Mai Education Sandbox. Phase 2, used include group interview records to gather data form 8 qualified individuals. Phase 3, the appropriateness of the guidelines is verified through a guideline’s assessment form. The target group, consisting of 29 users and 9 qualified individuals. Data analysis involves using percentages, averages, standard deviations, and content analysis. The study findings: 1.Problems and collaborative needs in Cooperative Learning are moderate overall. The most significant problem lies in operational collaboration, while the highest need for collaboration is in operational collaboration. 2.guidelines for cooperative learning management including understanding and adhering to the Educational Innovation Arae Act, linking and understanding contextual needs, creating an inclusive environment for genuine input, establishing Memorandums of Understanding, clarifying performance indicators and assessment criteria, and fostering a supportive environment to stimulate creativity. 3.The validity of guidelines for cooperative learning management is predominantly highest, with overall suitability, feasibility, and benefits also rated high.